2019
DOI: 10.1002/ps.5642
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota metabolic potential correlates with body size between mulberry‐feeding lepidopteran pest species

Abstract: BACKGROUND Many insect pests rely on microbial symbionts to obtain nutrients or for defence, thereby allowing them to exploit novel food sources and degrade environmental xenobiotics, including pesticides. Although Lepidoptera is one of the most diverse insect taxa and includes important agricultural pests, lepidopteran microbiotas, particularly functional traits, have not been studied widely. Here, we provide a comprehensive characterization of the gut microbiota across multiple mulberry‐feeding lepidopteran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 77 publications
1
17
0
Order By: Relevance
“…However, in the two treatment groups that fed on an artificial feed and plums, the following four phyla were dominant: Proteobacteria, Firmicutes, Bacteroidota, and Actinobacteriota. Many studies have reported that Proteobacteria and Firmicutes are the dominant bacterial phyla in insect gut bacterial communities, especially Lepidoptera [34,[41][42][43][44]. They play a key role in carbohydrate metabolism, amino acid metabolism, and membrane transport pathways of the host [20,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the two treatment groups that fed on an artificial feed and plums, the following four phyla were dominant: Proteobacteria, Firmicutes, Bacteroidota, and Actinobacteriota. Many studies have reported that Proteobacteria and Firmicutes are the dominant bacterial phyla in insect gut bacterial communities, especially Lepidoptera [34,[41][42][43][44]. They play a key role in carbohydrate metabolism, amino acid metabolism, and membrane transport pathways of the host [20,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the extracellular gut microbiota, complex microbial communities inhabiting the digestive tracts have also been studied in a wide variety of insects, such as termites [17][18][19], cockroaches, crickets, beetles [20,21], lepidopterans [22,23], hymenopterans [24] and Drosophila [25]. These studies revealed that the nature, diversity, complexity and functions of the gut microbiota are highly variable across the different groups of class Insecta [7].…”
Section: Bacterial Symbiosis In Insectsmentioning
confidence: 99%
“…Insects comprise numerous species, have various habitats and use diverse foods ( Basset et al 2012 , Shi et al 2010 ) and thus have correspondingly evolved diverse gut characteristics and microbiota ( Engel and Moran 2013 ). Some gut microorganisms improve the host’s nutritional, digestive and reproductive fitness and even pathogen defence ( Chen et al 2020 , Douglas 2015 , Engel and Moran 2013 , Liu et al 2020 , Wang et al 2020 ). Gut microbial composition of insects are largely affected by host feeding habits ( Colman et al 2012 , Wang et al 2020 , Liu et al 2020 , Yun et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbial composition of insects are largely affected by host feeding habits ( Colman et al 2012 , Wang et al 2020 , Liu et al 2020 , Yun et al 2014 ). Moreover, gut microbiota can vary when insects feed on different plant parts of the same host species ( Chen et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%